Human resource practices and organisational performance: Can the HRM-performance linkage be explained by the cooperative nehaviours of employees? - Mattijs Lambooij; Karin Sanders; Ferry Koster; Marieke Zwiers (Management Revue, 2006)
This paper addresses the question as to whether the linkage between HRM and organisational performance can be explained by the effect of the internal and strategic fit of HRM on the cooperative behaviours of employees. We expect that the more HRM practices are aligned within themselves (internal fit) and the more HRM is aligned with an organisation's strategy (strategic fit), the better employees know what is expected of them, and the more they behave cooperatively towards their co-workers and towards their supervisor. Next, we hypothesised that the cooperative behaviours of employees are positively related to the financial and non-financial performance of the organisation. These hypotheses were tested using multilevel regression (N=723 employees; 10 organisations). We found that cooperation with co-workers is negatively related to turn over and positively related to sick leave. No support was found, however, for the hypothesis that a better internal and strategic fit leads to more cooperative behaviour on the part of employees. The implications of these findings for future research and for human resource management are discussed.
Keywords: 650; cooperative behaviour; organisational performance; internal fit; strategic fit; mutual-investment model